Functional analysis through calculus

Algebra Level 4

Let f : R R f : \mathbb {R\to R} satisfy the equation

( x y ) f ( x + y ) ( x + y ) f ( x y ) = 4 x y ( x 2 y 2 ) x , y R \large ( x - y) f(x + y) - (x + y) f (x - y) = 4xy\left( { x }^{ 2 } - { y }^{ 2 } \right) \quad \forall x,y \in \mathbb R .

If f ( 1 ) = 2 f(1) = -2 , then find the absolute value of difference between maximum and minimum value of f ( x ) f(x) on the interval [ 3 , 3 ] \left[ -\sqrt { 3 } , \sqrt { 3 } \right] .


The answer is 4.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

( x y ) f ( x + y ) ( x + y ) f ( x y ) = 4 x y ( x 2 y 2 ) Let y = x 1 f ( 2 x 1 ) ( 2 x 1 ) f ( 1 ) = 4 x ( x 1 ) ( x y ) ( x + y ) Given that f ( 1 ) = 2 f ( 2 x 1 ) + 2 ( 2 x 1 ) = ( 4 x 2 4 x ) ( 2 x 1 ) f ( 2 x 1 ) = ( 2 x 1 ) ( 4 x 2 4 x 2 ) f ( 2 x 1 ) = ( 2 x 1 ) ( ( 2 x 1 ) 2 3 ) Replace 2 x 1 with x . f ( x ) = x ( x 2 3 ) \begin{aligned} (x-y)f(x+y) - (x+y) f(x-y) & = 4xy(x^2-y^2) & \small \color{#3D99F6} \text{Let } y = x-1 \\ f(2x-1) - (2x-1)\color{#3D99F6}f(1) & = 4x(x-1)(x-y)(x+y) & \small \color{#3D99F6} \text{Given that }f(1) = -2 \\ f(2x-1) + {\color{#3D99F6}2}(2x-1) & = (4x^2-4x)(2x-1) \\ f(2x-1) & = (2x-1)(4x^2-4x - 2) \\ f{\color{#3D99F6}(2x-1)} & = {\color{#3D99F6}(2x-1)}\left({\color{#3D99F6}(2x-1)}^2 - 3\right) & \small \color{#3D99F6} \text{Replace }2x-1 \text{ with }x. \\ \implies f({\color{#3D99F6}x}) & = {\color{#3D99F6}x}\left({\color{#3D99F6}x}^2 - 3\right) \end{aligned}

Note that f ( ± 3 ) = 0 f(\pm \sqrt 3) = 0 . The local maximum and minimun within [ 3 , 3 ] \left[-\sqrt 3, \sqrt 3\right] are when d d x f ( x ) = 3 x 2 3 = 0 \dfrac d{dx}f(x) = 3x^2 - 3 = 0 or x = ± 1 x = \pm 1 . Since d 2 d x f ( x ) = 6 x \dfrac {d^2}{dx}f(x) = 6x . f ( 1 ) = 1 ( ( 1 ) 2 3 ) = 2 f(-1) = -1\left((-1)^2-3\right) = 2 is the local maximum and f ( 1 ) = 1 ( 1 2 3 ) = 2 f(1) = 1\left(1^2-3\right) = -2 . the minimum. Therefore, 2 ( 2 ) = 4 |2-(-2)| = \boxed{4} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...